Corruption and Oil Rent: an Empirical Analysis of Panel Data - Monsalve Farías, Daniela; Gómez Domínguez, José Gregorio; Puente Camba, José Manuel (Revista del CLAD Reforma y Democracia, 2022)
For some countries, having abundant natural resources such as oil has become a catalyst for economic development. However, for other countries this has ceased to be a blessing and has become a phenomenon characterized by unfavorable economic and institutional performance. This paradox is known as the curse of natural resources and has been studied by various authors since the 19th century. Corruption is among the main causes involved in this dynamic, affecting the efficient distribution of resources and long-term economic growth. The purpose of this study is to analyze the hypothesis that oil revenue increases corruption and whether this relationship is maintained depending on institutional and economic variables. It also determines whether there is a difference between the OPEC and non-OPEC member countries. To address the research questions, a main econometric model and two auxiliary models are developed. The first includes variables linked to the oil sector; the second incorporates institutional variables such as accountability, regulatory framework and political stability; and the third considers variables that capture the macroeconomic environment of the countries. The work is carried out during the period 1990-2017 and includes a sample of 47 countries, where 28% belong to OPEC. A panel data model is used through the minimum generalized squares methodology (FGLS) to make a more robust estimation. As the most relevant finding of the study, it was obtained that, with an increase of 1 percentage point in oil revenue as a percentage of GDP, the corruption index increases by 0.001806 units, this result being statistically significant at 1%. Similarly, when control variables at the institutional level and the macroeconomic environment are included, the relationship between oil revenue and corruption remains statistically significant. Finally, it was not possible to empirically prove that there is a significant difference between this relationship when discriminating between OPEC and non-OPEC countries.
Keywords: Administrative Corruption; Petroleum; Petroleum Industry; OPEC; Economical Analysis; Institutional Analysis